Using relative handgrip strength to identify children at risk of sarcopenic obesity - Gontarev, Seryozha; Jakimovski, Mirko; Georgiev, Georgi (ARAN Ediciones, 2020)
Background: identifying children at risk of developing childhood sarcopenic obesity often requires specialized equipment and expensive testing procedures, so cheaper and quicker methods would be advantageous, especially in field-based settings. Objective: the purpose of this study was to determine the relationships between the muscle-to-fat ratio (MFR) and relative handgrip strength, and to determine the ability of handgrip strength relative to body mass index (grip-to-BMI) to identify children who are at risk of developing sarcopenic obesity. Material and method: grip-to-BMI was measured in 4021 Macedonian children (6 to 10 yrs). Bioelectrical impedance was used to estimate body fat mass and skeletal muscle mass, from which the MFR was calculated. Results: the area under the curve (AUC) was 0.771 (95 % CI, 0.752 to 0.789, p < 0.001) in girls 6-10 years old and 0.843 (95 % CI, 0.826 to 0.859, p < 0.001) in boys 6-10 years old. Calculated using the grip-to-BMI ratio, the OR (95 % CI) for girls to be at risk of sarcopenic obesity identified by MFR was 20.182 (10.728-37.966, p < 0.001) and was 16.863 (10.782-26.371, p < 0.001) for boys. Conclusion: the grip-to-BMI ratio can be used to predict the presence of sarcopenic obesity in children, which can play a role in pediatric health interventions.
Keywords: Bioelectrical impedance. Fat-free mass. Skeletal muscle mass. Muscle fat ratio.